Performance of channel codes in wireless communication systems using efficient simulation - Sebastião, P. J. A. (2011)
With the widespread of new radio systems, it is essential that their performance is evaluated prior to auxiliary design and commercial development. Although there are many methods to model and estimate the performance of a given radio system with some accuracy, most of these methods require high computational resources or long simulation times. In this study, the authors present a general and efficient simulation method for estimating the performance of a wireless communication systems, with particular emphasis for its forward error correction sub-system when using block channel codes, for channels affected by additive white Gaussian noise, free space attenuation, shadowing, fading and interfering sources. Both soft-decision (SD) and hard-decision (HD) decoding are considered and the overall performance takes into account modulation, coding and channel conditions. This efficient simulation is compared with the Monte Carlo simulation method and its performance is assessed for the Tomlinson, Cercas and Hughes code family. This new simulation method has an temporal efficiency of two or three orders of magnitude for SD and HD and three or four orders, considering a bit-error-ratio of 0.01 and 0.001%, respectively.